ANALYSIS OF THE PRINCIPLES AND LEGAL PROVISIONS OF LAW NO. 20 OF 2003 ON THE NATIONAL EDUCATION SYSTEM AS THE FOUNDATION FOR NATIONAL EDUCATION POLICY - Aslan Aslan; Abbas Abbas (Adisam Publisher, 2025)
Law No. 20 of 2003 on the National Education System is the main legal basis governing the implementation of education in Indonesia. This study aims to analyse the principles and legal provisions in the law and their implications as the basis for national education policy. The research method used is a literature review with a juridical-normative approach to legislation and related literature. The results of the study show that the legal principles contained in Law No. 20 of 2003 affirm education as a fundamental right that is fair, democratic, inclusive, and sustainable. The provisions of important articles in this law provide a comprehensive normative framework to ensure quality, equity, and effective management of education. This law serves as a strategic foundation for the formulation and implementation of national education policies that are adaptive to social dynamics and the nation's development needs.